2011
DOI: 10.1016/s1413-8670(11)70184-2
|View full text |Cite
|
Sign up to set email alerts
|

Physician adherence to guidelines for tuberculosis and HIV care in Rio de Janeiro, Brazil

Abstract: Physicians are substantially more compliant with HIV monitoring and PCP prophylaxis than with TB prophylaxis guidelines. Efforts to improve TB control in HIV patients are badly needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…Our finding is similar to the observation by Saraceni et al 10 who noted non compliance with TB prophylaxis guidelines in brazil and opined that efforts to improve TB control in HIV patients were badly needed. Non compliance with guidelines could be a consequence of poor understanding of the guidelines by the attending clinicians or a communication gap between the wards, the DOTS clinic and the HIV clinic.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding is similar to the observation by Saraceni et al 10 who noted non compliance with TB prophylaxis guidelines in brazil and opined that efforts to improve TB control in HIV patients were badly needed. Non compliance with guidelines could be a consequence of poor understanding of the guidelines by the attending clinicians or a communication gap between the wards, the DOTS clinic and the HIV clinic.…”
Section: Discussionsupporting
confidence: 92%
“…This fact is in concordance with the study of Saraceni et al 17 , who observed the involvement of health care professionals in the treatment of HIV infection, in contrast with the lack of attention that has been paid to the detection and treatment of LTB i in PLWHA. These results, along with those of the present study point to the need for new strategies in order to raise awareness among health professionals working in specialized services for HIV/AIDS for the preventive treatment of tuberculosis.…”
Section: Discussionsupporting
confidence: 91%
“…The involvement of attending physicians is fundamental for patient adherence to treatments and for recognizing behavior known to be associated with non-adherence 17 . In Quebec city, Canada, primary care physicians initiated a substantial number of LTB i treatments, but less than half of patients completed treatment regardless of the physician specialty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brazil has a high burden of TB in PLHIV 12,13,14 , with most recent estimates stating that 9% of HIV deaths are due to TB 15 . Brazilian guidelines recommending tuberculin skin tests and isoniazid preventive therapy for PLHIV have existed since 1995 16 and recent recommendations from the World Health Organization restate the need for IPT for PLHIV, though evidence in Brazil suggests that physicians do not adhere strictly to these guidelines 17 .…”
Section: Introductionmentioning
confidence: 99%